Prevalence and correlations of temporomandibular disorders in Northern Jordan using diagnostic criteria axis I. Issue 2 (20th January 2019) - Alrashdan, Mohammad S.; Nuseir, Amjad; AL‐Omiri, Mahmoud K.
Abstract: Aim: The aim of the present study was to document the prevalence and possible correlations of temporomandibular disorders (TMD) in a sample of participants from Northern Jordan. Methods: A total of 368 adult participants were consecutively selected from visitors to a major health facility in Northern Jordan and examined according to the diagnostic criteria (DC) for TMD (DC/TMD) protocol. Patients with conditions that could interfere with TMD diagnosis were excluded. Pearson correlation and analysis of variance statistical tests were applied. Statistical significance was set at P  ≤   0.05, with a 95% confidence interval. Results: A total of 98 patients (26.7%) had 1 TMD diagnoses; 60 participants (16.3%) had a pain‐related TMD diagnosis, 48 (13%) had intra‐articular joint disorders (IAD), and 16 had both pain‐related TMD and IAD. In addition, six (1.6%) participants were found to have degenerative joint disease. Females were found to have a higher prevalence of pain‐related TMD diagnoses ( r  = 0.111, P  =   0.034) and headache ( r  = 0.129, P  =   0.013) than males. Clicking was positively related to both pain‐related TMD ( r  = 0.154, P  =   0.003) and IAD ( r  = 0.576, P  =   0.000). Conclusion: The frequency of TMD and related features was reported in a Northern Jordanian population using DC/TMD for the first time, and the results are comparable to other populations in similar study settings.